Theoretical Issues with New Actors and Emergent Modes of Labour Regulation - Legault, Marie-Josée; Bellemare, Guy (Relations industrielles / Industrial Relations, 2008)
As the global economy undergoes a major transformation, the inadequacy of labour relations theories dating back to Fordism, especially the systemic analysis model (Dunlop, 1958) and the strategic model (Kochan, Katz and McKersie, 1986), in which only three actors—union, employer and State—share the stage is becoming increasingly obvious. A good example is provided by companies offering information technology services to businesses, where new means of regulation emerge and illustrate the need to incorporate new actors and new issues if we are to account for its contemporary complexity. A survey of 88 professionals has revealed regulation practices that call into question the traditional boundaries of the industrial relations system from two points of view: that of the three main actors, by bringing the customer and work teams onto the stage, and that of the distinction between the contexts and the system itself.